Ticks and bacterial tick-borne pathogens in Piemonte region, Northwest Italy - Pistone, Dario; Pajoro, Massimo; Novakova, Eva; Vicari, Nadia; Gaiardelli, Cesare; Viganò, Roberto; Luzzago, Camilla; Montagna, Matteo; Lanfranchi, Paolo (Experimental & applied acarology, 2017)
A molecular screening for tick-borne pathogens was carried out in engorged and in questing ticks collected in Verbano Cusio Ossola county, Piemonte region, Italy. Engorged ticks were removed from wild and domestic animal hosts. The most abundant and common tick species in the area was Ixodes ricinus (192 adults, 907 nymphs). Few individuals of Ixodes hexagonus (15) and Rhipicephalus sanguineus (7) were found among the ticks removed from domestic animals (46 examined ticks). The presence of Rickettsia spp., Borrelia burgdorferi sensu latu, Francisella tularensis and Coxiella burnetii was evaluated by PCR and sequencing in 392 individuals of I. ricinus (adult and nymphal stages) and 22 individuals of the two other tick species. Five Borrelia species (i.e. B. burgdorferi sensu stricto, B. garinii, B. afzelii, B. valaisiana and B. lusitaniae), proved or suspected to cause clinical manifestations of Lyme disease in humans, showed 10.5 and 2.2% combined prevalence in questing and engorged I. ricinus, respectively. In addition, two species of rickettsiae (R. helvetica and R. monacensis) were identified and reported with 14.5 and 24.8% overall prevalence in questing and in engorged ticks. The prevalence of F. tularensis in the ticks collected on two wild ungulate species (Capreolus capreolus and Cervus elaphus) was 5.7%. This work provided further data and broadened our knowledge on bacterial pathogens present in ticks in Northwest Italy.
Keywords: polymerázová řetězová reakce; Male; klíště; Rhipicephalus sanguineus; Rickettsia helvetica; Nymph; Animals, Wild; Bacteria; Bacterial Physiological Phenomena; divoká zvířata; Borrelia burgdorferi sl; mužské pohlaví; Itálie; Piemonte; nymfa; larva; Animals; hospodářská zvířata; ženské pohlaví; Animals, Domestic; zvířata; Ixodes; Verbano Cusio Ossola; Polymerase Chain Reaction; Larva; Italy; Female; Francisella tularensis; fyziologie bakterií; Rickettsia monacensis